B-Vitamins and One-Carbon Metabolism - Kristina Pentieva (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Folate, vitamin B12, vitamin B6 and riboflavin play a key role as coenzymes in one-carbon metabolism which, in turn, is essential for a broad range of fundamental physiological processes, including RNA and DNA synthesis, cell division, tissue growth and methylation. Deficiencies or imbalance of B-vitamins, as well as genetic polymorphisms and environmental factors, are shown to disturb the normal function of one-carbon metabolism with adverse effects on human health. Although a vast volume of research has already been conducted in this area, there are still significant gaps in our knowledge that require further investigations. This Special Issue of Nutrients invited submission of manuscripts, original research or reviews of the scientific literature, focused on novel findings in relation to B-vitamins and one-carbon metabolism in terms of: metabolic roles and molecular mechanisms; gene-nutrient interactions; fetal growth and programing; risk of disease (birth defects and pregnancy related conditions, cancer, cardiovascular disease and hypertension, neuropsychiatric disease, osteoporosis); health effects of B-vitamin supplementation and food fortification.